Prevalence and determinants of zoonotic malaria in the Greater Mekong Subregion (GMS) and Malaysia: systematic review and meta-analysis - Alex Ahebwa; Chutipong Sukkanon; Jeffrey Hii; Ratchadawan Ngoen-Klan; Uraiwan Arunyawat; Sylvie Manguin; Theeraphap Chareonviriyaphap (Malaria Journal)
Abstract Background Zoonotic malaria is a growing public health concern in Southeast Asia, with Malaysia and Thailand accounting for 95.2% of the 3290 global cases reported in 2023. It is caused by Plasmodium species primarily adapted to long- and pig-tailed macaques, transmitted to humans via certain Anopheles mosquitoes. This meta-analysis quantifies its prevalence and risk factors in the Greater Mekong Subregion and Malaysia. Methods This meta-analysis was conducted following the PRISMA (Preferred Reporting Items for Systematic) guidelines. A comprehensive literature search was conducted in PubMed and Scopus databases (2000–2024) to identify studies on zoonotic malaria infection in humans and monkeys. Backward search was done using Google Scholar. Inclusion criteria were defined using the CoCoPop (Condition, Context, and Population) framework. Two reviewers independently extracted data, and study quality was assessed using appropriate risk-of-bias tools. A random-effects meta-analysis was conducted using the metafor package in R programme, with heterogeneity assessed via I 2 statistics and subgroup analyses. Meta-regression using a linear mixed-effects models estimated unadjusted odds ratios for transmission determinants. Results The overall pooled prevalence of malaria infection was 8.6% in humans and 35.0% in monkeys. The pooled prevalence was higher in Malaysia (22.8%) than GMS (1.2%). In GMS, Myanmar with a pooled prevalence of 4.9% contributes a higher burden of human zoonotic malaria than Thailand (1.8%). Significantly high heterogeneity between studies was recorded for both human (I 2  = 99.7%, P < 0.0001) and monkey (I 2  = 98.7%, P < 0.0001) infections. The major risk factors assessed were gender (males: OR = 4.3), age (adults 21–40 years: OR = 5.6), mobility, misdiagnosis, and Plasmodium knowlesi infection. Most cases (4773; 89.6%) were initially misdiagnosed by microscopy as non-zoonotic. Prevalence in monkeys was highest in Macaca nemestrina (63.3%) followed by Macaca fascicularis (31.4%) with Plasmodium inui and Plasmodium cynomolgi as the most frequent parasites. Conclusions This study contributes to the understanding of the transmission complexities of zoonotic malaria in the GMS countries and Malaysia, highlighting critical knowledge gaps and the need for a multidisciplinary approach to managing its further spread.